AN ANALYSIS OF EFL WRITING DEVELOPMENT OF UNDERGRADUATE ENGLISH EDUCATION DEPARTMENT STUDENTS: AN INDONESIAN CONTEXT - Tans Feliks; Agustinus Semiun; Hilda M Nalley (Academic Journal of Educational Sciences, 2019)
This research aims at finding out: 1) kinds of English-as-a-foreign-language (EFL) essays written by the fourth semester students of the Undergraduate English Education Department, School of Teachers Training and Educational Sciences, Nusa Cendana University; 2) how the students develop as EFL student writers; 3) elements of EFL writing that the students can produce well; and, 4) elements of EFL writing that the students fail to produce well. This research using desctiptive-qualitative method was conducted from March to September, 2019. Its research subjects were the fourth semester students of the department. Since the department has four classes, the researchers chose two classes purposively as their research subjects. The instruments used to get the data were writing tests conducted twice, that is, the first one on 18 March and the second one on 18 September, 2019. In doing the first test, the students were each asked to individually handwrite an essay whose topic was free for an hour. In writing their essays, the students were not allowed to use any dictionary and they were not allowed to discuss it with their friends. After it was written, the researchers collected the essays, asked the students for clarrification on their unclear hand writings. Six months later, that is, on 18 September, 2019, the same essays were handed back to be revised/edited by their relevant writers. The time used to edit/revise each essay by each relevant writer was an hour and they were not allowed to use a dictionary or to discuss it with their friend(s). In addition to these writing tests, the researchers also studied the students’ curriculum document to have an insight into any courses they join that could have influenced their writing development. The focus of the researchers’ documentary study was on subjects related to EFL writing. The data were analyzed descriptively focussing on four major elements of EFL writing, namely: content; organization; word choice, sentence structures, and paragraph structures; and, mechanics of writing (i.e. punctuations and spelling). The data collected were analysed descriptively. It is found that students produced three major kinds of written products, that is, informative, expressive, and a combination of both, but none was included in creative writing. The students had two distinctive ways of development, that is, good and poor development in terms of content; organization; word choice, sentence structures, and paragraph structures; and, mechanics of their writings (i.e. punctuations and spelling). The elements of EFL writings that develop well and/or poorly vary among the research students: some develop well, for example, in relation to content, but poor on word choice and other elements of EFL writing.